Interv'iu s IUriem Norshteinom . Interv'iu s IUriem Norshteinom . Interview with IUrii Norshtein . Интервью с Юрием Норштейном - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with IUrii Norshtein about art, philanthropy, and his work. Featured in the program: Norshtein, IUrii Borisovich (Animation Films Director) Интервью об искусстве, филантропии и творчестве. В программе участвуют: Норштейн, Юрий Борисович (Режиссер анимационного кино)